Preparation method for improving strength of aggregate
By modifying with nano-silica fume, vacuum-assisted polymer impregnation, and treating with silane coupling agents, the problems of insufficient aggregate strength and interfacial adhesion were solved, significantly improving the compressive strength and durability of the aggregate and enhancing the overall performance of the composite material.
Patent Information
- Application Number
- CN202411521332.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-07
Smart Images

Figure CN119263679A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, in particular to a preparation method for improving aggregate strength. Background Art
[0002] In the field of building materials, aggregates are an important component of composite materials such as concrete and asphalt mixtures, and their performance directly affects the strength, durability and crack resistance of the entire structural material. However, traditional aggregates usually have problems with insufficient strength and durability in their natural state, especially in complex environments (such as freeze-thaw cycles, chemical corrosion, etc.), which are prone to deterioration, resulting in reduced structural performance and shortened service life. These problems are particularly prominent in high-strength building materials such as ultra-high performance concrete (UHPC), which puts higher requirements on aggregates.
[0003] In the prior art, methods for improving the strength of aggregates mainly focus on surface treatment or adding modifiers. For example, the performance of the aggregate surface is improved by using ordinary silica fume or coating the surface with certain chemical materials. However, due to the large particle size of traditional silica fume, it cannot fully penetrate into the microporous structure of the aggregate, resulting in limited modification effect and failure to significantly improve the overall strength and durability of the aggregate. In addition, the effect of ordinary surface coating treatment is usually limited to the surface layer, and it is impossible to deeply enhance the pore structure inside the aggregate, which makes it easy for internal cracks to expand when the aggregate is subjected to stress, reducing the compressive strength.
[0004] In addition, the existing technology is also insufficient in the interfacial bonding between aggregate and matrix material. Microcracks or pores are easily formed at the interface between aggregate and cement matrix material. Especially when high-strength concrete is used, these interface problems become the starting point for the destruction of the entire composite material, seriously affecting the long-term performance of the material. Therefore, how to effectively improve the interfacial bonding of aggregates while improving their strength and durability has become a problem to be solved in the field of building materials. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a preparation method for improving the strength of aggregate, which solves the problems of insufficient strength, poor durability and low interface bonding with the matrix material of the prior art aggregate.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: A preparation method for improving aggregate strength comprises the following steps:
[0007] 1) Select natural coarse aggregate with a particle size of 5-20 mm and perform pretreatment of cleaning, alkali solution soaking and drying;
[0008] 2) Soak the pretreated aggregate in 8-12 mol / L NaOH solution for 60-120 minutes and modify it with nano-silica fume;
[0009] 3) heat treating the aggregate at 70-100°C for 3-5 hours to generate CSH gel;
[0010] 4) Place the dried aggregate in a vacuum environment of 0.1-0.3 bar, add nano polyurethane or epoxy resin polymer solution, and immerse for 60-90 minutes;
[0011] 5) Curing the polymer-impregnated aggregate at 20-25°C for 12-24 hours;
[0012] 6) Spraying the aggregate surface after polymer curing with 3-5% silane coupling agent solution and air drying for 6-12 hours.
[0013] Preferably, the pretreatment comprises:
[0014] Use distilled water to wash for 20-30 minutes to remove impurities on the surface of the aggregate;
[0015] Soak the cleaned aggregate in 0.5M NaOH solution at a temperature of 25-35°C for 10-20 minutes;
[0016] After soaking in alkali solution, the aggregate is repeatedly washed with distilled water until the pH value of the filtrate is close to neutral, and then dried at 60-80℃.
[0017] Preferably, in the nano-silica fume modification step, the particle size of the nano-silica fume is 50-100 nm, and it is added at 3-7% of the mass of the aggregate, and is evenly dispersed in the solution by ultrasonic dispersion and stirring.
[0018] Preferably, in the modification of the nano-silica fume, the nano-silica fume solution further contains 1-2% sodium silicate.
[0019] Preferably, in the polymer impregnation step, the vacuum degree is set to 0.1-0.3 bar, the impregnation time is 60-90 minutes, and a low-frequency vibration device is used with a frequency of 5-10 Hz.
[0020] Preferably, a nano-reinforcement material is further added to the polymer solution. The nano-reinforcement material is nano-titanium dioxide or nano-zinc oxide, and the addition ratio is 1-3% of the mass of the polymer solution.
[0021] Preferably, the polymer curing step comprises curing at room temperature of 20-25° C. for 12-24 hours, or thermal curing at 50-80° C. for 4-8 hours.
[0022] Preferably, the step 6) comprises spraying a 3-5% concentration of a silane coupling agent solution on the aggregate surface with a spraying thickness of 20-40 μm, and air-drying at 20-25° C. for 6-12 hours.
[0023] The invention also provides a reinforced aggregate, which is prepared by the method.
[0024] The present invention also provides a method for preparing a reinforced concrete, comprising applying the reinforced aggregate to a cement-based composite material.
[0025] The present invention provides a preparation method for improving aggregate strength. It has the following beneficial effects:
[0026] 1. The present invention generates dense CSH gel on the surface and internal pores of aggregates through chemical modification of nano-silica fume. This gel fills the micropores and cracks of the aggregate, making the aggregate structure more compact and strong, and significantly improving the compressive strength of the aggregate. Compared with traditional silica fume modification, nano-silica fume can deeply fill the tiny pores of aggregates due to its smaller particle size and higher reactivity, producing a more significant strength enhancement effect.
[0027] 2. The present invention fills aggregate micropores with nano-silica fume and combines vacuum-assisted polymer impregnation to form a uniform and dense protective film, which effectively prevents the penetration and accumulation of water inside the aggregate and reduces the expansion pressure of water during freeze-thaw cycles. This greatly reduces the degradation of aggregates during freeze-thaw cycles and improves their freeze-thaw resistance and long-term durability.
[0028] 3. The present invention forms active functional groups on the aggregate surface through the interface enhancement treatment of silane coupling agent, and these functional groups can form strong chemical bonds with the chemical groups in the matrix material. This enhancement measure significantly improves the bonding force between the aggregate and the cement matrix material, avoids the generation of cracks at the interface, and improves the overall structural performance of the composite material.
[0029] 4. The present invention allows the polymer to penetrate into the micropores and cracks inside the aggregate, forming a dense cross-linked network structure. This polymer layer provides a dual enhancement effect of strength and toughness after curing, especially in terms of resisting crack propagation and fatigue damage, showing significant advantages.
[0030] 5. The preparation method of the present invention forms a multi-level reinforcement mechanism by combining nano-silica fume modification, vacuum-assisted impregnation and silane coupling agent treatment. The process can flexibly adjust each process step according to different application requirements, for example, it is suitable for a variety of engineering materials such as high-strength concrete, ultra-high performance concrete (UHPC), prefabricated components, asphalt mixtures, etc., showing high applicability and production flexibility. At the same time, the process steps are simple, easy to promote industrialization, and the cost is relatively low. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 It is a schematic diagram of the process flow of the present invention. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Please refer to the attached Figure 1 The present invention provides a preparation method for improving the strength of aggregates, which aims to significantly improve the strength, durability and interface bonding performance of aggregates through a composite treatment technology of chemical modification and polymer impregnation. The following describes the implementation of the present invention in detail in conjunction with specific steps.
[0034] 1. Aggregate pretreatment
[0035] Select natural coarse aggregate (such as basalt or granite) with a particle size of 5-20mm, and pre-treat it to remove surface impurities and activate the aggregate surface. The specific steps are as follows:
[0036] 1) Cleaning: Place the selected aggregate in distilled water for cleaning, and the cleaning time is controlled within 20-30 minutes. Use mechanical stirring or ultrasonic vibration cleaning equipment (frequency set to 20-40kHz) to ensure that impurities such as sand, oil and other impurities on the surface of the aggregate are completely removed.
[0037] 2) Alkali solution soaking: Soak the cleaned aggregate in 0.5M NaOH solution at a temperature of 25-35°C for 10-20 minutes. The purpose of this step is to remove organic matter attached to the surface of the aggregate through the alkali solution and enhance the activity of the aggregate surface.
[0038] 3) Rinse and dry: After soaking, rinse the aggregate repeatedly with distilled water until the pH value of the filtrate is close to neutral (pH = 7-8). Then place the aggregate in an oven at 60-80°C for 6 hours to ensure that there is no residual moisture on the surface of the aggregate, providing the best conditions for subsequent processing.
[0039] 2. Chemical modification
[0040] 1) Soaking in NaOH solution: Soak the pretreated aggregate in 8-12mol / L NaOH solution for 60-120 minutes, during which mechanical stirring is used to ensure that the NaOH solution can evenly penetrate the surface of the aggregate. The concentration and soaking time of the NaOH solution can be appropriately adjusted according to the type and surface characteristics of the aggregate. The NaOH solution can remove calcium compounds on the surface of the aggregate, activate the functional groups on the surface, and create conditions for the subsequent binding of nano-silica fume.
[0041] 2) Nano-silica fume modification: Add nano-silica fume (particle size 50-100nm) to distilled water at a ratio of 3-7% of the mass of the aggregate to prepare a silica fume solution. Use an ultrasonic disperser (power setting of 100-200W) combined with a magnetic stirrer (speed 1000-3000rpm) to stir and disperse for 30-60 minutes to ensure the uniformity and dispersibility of the nano-silica fume in the solution. Add 1-2% sodium silicate (Na2SiO3) to the nano-silica fume solution to promote the reaction between the nano-silica fume and the aggregate surface through the activation of sodium silicate, thereby improving the strength and durability of the aggregate.
[0042] 3) Aggregate impregnation: Soak the NaOH-treated aggregate in the nano-silica fume solution for 30-60 minutes and perform low-frequency vibration (the frequency is set to 5-10 Hz) to ensure that the nano-silica fume evenly penetrates the aggregate surface and internal pores.
[0043] 3. Heat treatment
[0044] The aggregate impregnated with nano-silica fume is placed in an oven at 70-100°C for heat treatment for 3-5 hours. Through this process, the active silica in the nano-silica fume reacts with the calcium ions in the aggregate to form CSH gel. The gel fills the micropores of the aggregate and improves the compactness and mechanical properties of the aggregate. The choice of heat treatment temperature and time has a direct impact on the generation rate and structural stability of the CSH gel.
[0045] 4. Polymer impregnation
[0046] 1) Vacuum-assisted polymer impregnation: The heat-treated aggregate is cooled to room temperature and then placed in a vacuum impregnation device with a vacuum degree set to 0.1-0.3 bar and maintained in a vacuum state. The nano-polyurethane or epoxy resin polymer solution is slowly injected into the vacuum system and the impregnation time is controlled at 60-90 minutes. Vacuum impregnation helps the polymer fully penetrate into the internal pores of the aggregate, further improving the strength of the aggregate.
[0047] 2) Preparation of polymer solution: Add nano-reinforcement materials (such as nano-titanium dioxide or nano-zinc oxide) to the nano-polyurethane or epoxy resin solution at 1-3% by mass, stir evenly and use it as the polymer solution for impregnation. The nano-reinforcement materials further improve the anti-aging and wear resistance of the polymer, ensuring the long-term durability of the aggregate.
[0048] 5. Polymer curing
[0049] 1) Room temperature curing: The aggregate impregnated with polymer is restored to normal pressure and cured naturally in an environment of 20-25°C for 12-24 hours. Room temperature curing can ensure that the cross-linking reaction of the polymer is fully completed to form a dense network structure.
[0050] 2) Heat curing (optional): If you need to speed up the production process or increase the hardness of the polymer on the aggregate surface, you can choose to heat cure the aggregate in an environment of 50-80°C for 4-8 hours. This process helps to quickly enhance the mechanical properties of the polymer.
[0051] 6. Interface enhancement
[0052] After the polymer is cured, the aggregate is sprayed with a 3-5% silane coupling agent solution. The spraying thickness is controlled at 20-40μm to ensure that the coupling agent evenly covers the aggregate surface. The role of the silane coupling agent is to enhance the interfacial adhesion between the aggregate and the matrix material and improve its mechanical properties in cement-based composites. After spraying, the aggregate is air-dried at 20-25℃ for 6-12 hours to ensure that the coupling agent fully reacts with the aggregate surface.
[0053] The reinforced aggregate prepared by the above steps can be widely used in cement-based composite materials such as concrete, ultra-high performance concrete (UHPC), mortar, asphalt mixture, etc. The reinforced aggregate exhibits higher compressive strength, durability and adhesion with the matrix material in the application, and is suitable for high-strength structural parts, prefabricated components, bridges and buildings.
[0054] The present invention uses nano-silica ash and alkali solution activation treatment, and the calcium compound on the surface of the aggregate reacts with the nano-silica ash to generate a volcanic ash reaction to generate CSH gel. This reaction effectively improves the compactness of the aggregate, and by filling the micro cracks on the surface and pores of the aggregate, the compressive strength and durability of the aggregate are enhanced. At the same time, the polymer impregnation technology is assisted by vacuum, so that the nano-enhanced polymer can penetrate deeply into the internal pores of the aggregate, further improving the mechanical properties of the aggregate. The dense network structure formed inside the aggregate after the nano-polymer is cured improves the tensile strength and fatigue resistance of the aggregate.
[0055] In addition, the interface strengthening effect of the silane coupling agent significantly improves the bonding strength between the aggregate and the cement-based material, avoids the problem of early cracks at the interface between the aggregate and the matrix, and improves the overall durability of the composite material. This multi-level strengthening mechanism enables the preparation method of the present invention to provide better performance in a wider range of application scenarios compared to traditional methods, especially for the demand for high-strength and high-durability building materials.
[0056] In order to better understand the present invention, the above method is described in detail below in conjunction with specific embodiments.
[0057] Example 1: Preparation of reinforced aggregate for high strength concrete
[0058] 1. Aggregate pretreatment
[0059] Select basalt aggregate with a particle size of 5-10 mm and wash it with distilled water for 25 minutes.
[0060] Soak in 0.5 M NaOH solution for 15 min, the temperature is controlled at 30 °C, and rinse repeatedly with distilled water to a pH of 7.
[0061] The drying condition is drying at 70°C for 6 hours.
[0062] 2. Chemical modification
[0063] Soak the aggregate in 10 mol / L NaOH solution for 90 minutes.
[0064] The particle size of nano-silica fume was controlled at 70 nm, and 5% of the mass of the aggregate was added into the solution. Ultrasonic dispersion was performed for 60 minutes, and the solution temperature was controlled at 28°C.
[0065] After soaking for 30 min, the aggregate was heat treated at 90 °C for 4 h to generate CSH gel.
[0066] 3. Polymer impregnation
[0067] In a vacuum environment of 0.2 bar, vacuum impregnation was performed using nano-polyurethane solution for 90 minutes.
[0068] Nano-titanium dioxide is added to the polymer solution at a ratio of 1.5% to enhance the polymer performance.
[0069] 4. Curing and interface enhancement
[0070] Curing at room temperature for 24 hours.
[0071] 3.5% silane coupling agent solution was sprayed on the aggregate surface with a spraying thickness of 30 μm and air-dried for 12 hours at 20°C.
[0072] Application: This reinforced aggregate is used in high-strength concrete structures, such as bridges and high-rise building structures, which significantly improves the compressive and tensile properties.
[0073] Example 2: Preparation of reinforced aggregate for ultra-high performance concrete (UHPC)
[0074] 1. Aggregate pretreatment
[0075] Granite aggregates with a particle size of 5-15 mm were selected and ultrasonically cleaned with distilled water for 30 minutes (the frequency was set to 25 kHz).
[0076] Soak in 0.5 M NaOH solution for 20 min at 25 °C and then rinse to pH 7.
[0077] The drying condition is drying at 80°C for 8 hours.
[0078] 2. Chemical modification
[0079] Soak the aggregate in 8 mol / L NaOH solution for 60 minutes.
[0080] The particle size of nano-silica fume is controlled at 60 nm, added into the solution at 7% of the mass of the aggregate, and dispersed by ultrasonic for 40 minutes.
[0081] After soaking for 45 min, the aggregate was heat treated at 80 °C for 5 h to generate a dense CSH gel layer.
[0082] 3. Polymer impregnation
[0083] The nano epoxy resin solution was vacuum impregnated in a 0.3 bar vacuum environment for 60 minutes.
[0084] Nano zinc oxide is added into the polymer solution in a proportion of 2%.
[0085] 4. Curing and interface enhancement
[0086] Heat cure at 50°C for 8 hours.
[0087] 3% silane coupling agent solution was sprayed on the aggregate surface with a spraying thickness of 25 μm and air-dried at 25°C for 6 hours.
[0088] Application: This reinforced aggregate is used in ultra-high performance concrete (UHPC) and is suitable for high-demand crack-proof and tensile-resistant structural parts such as tunnel linings and high-durability components.
[0089] Example 3: Preparation of reinforced aggregate for road paving asphalt mixture
[0090] 1. Aggregate pretreatment
[0091] Natural gravel aggregate with a particle size of 10-20 mm was selected, the cleaning time was 15 minutes, distilled water was used and surfactant was added to remove oil stains.
[0092] Soak in 0.5 M NaOH solution for 10 minutes, then rinse and dry at 60 °C for 6 hours.
[0093] 2. Chemical modification
[0094] Soak the aggregate in 12 mol / L NaOH solution for 120 minutes.
[0095] The particle size of nano-silica fume is controlled at 100 nm, added at 3% of the mass of the aggregate, and dispersed by ultrasonic for 30 minutes.
[0096] After soaking for 60 min, the aggregate was heat treated at 70 °C for 3 h to generate a CSH gel layer.
[0097] 3. Polymer impregnation
[0098] Under a vacuum environment of 0.1 bar, vacuum impregnation with nano-polyurethane solution was performed for 90 minutes to ensure deep penetration.
[0099] No nanoreinforcements were added to the polymer solution.
[0100] 4. Curing and interface enhancement
[0101] Curing at room temperature for 12 hours.
[0102] 4% silane coupling agent solution was sprayed on the aggregate surface with a spraying thickness of 35 μm and air-dried at 20°C for 6 hours.
[0103] Application: This reinforced aggregate is suitable for asphalt mixtures for road paving, especially high-strength compression-resistant pavements, to extend the service life of roads and improve crack resistance and wear resistance.
[0104] Example 4: Preparation of reinforced aggregate for precast component production
[0105] 1. Aggregate pretreatment
[0106] Select basalt aggregate with a particle size of 5-10 mm and wash it with distilled water for 20 minutes.
[0107] The samples were immersed in 0.5 M NaOH solution for 10 min, then rinsed and dried at 80 °C for 6 h.
[0108] 2. Chemical modification
[0109] Soak the aggregate in 10 mol / L NaOH solution for 90 minutes.
[0110] The particle size of nano-silica fume is controlled at 80nm, added at 5% of the mass of the aggregate, and ultrasonically dispersed for 60 minutes.
[0111] After soaking for 45 min, the aggregate was heat treated at 90 °C for 4 h to generate CSH gel.
[0112] 3. Polymer impregnation
[0113] Under a vacuum environment of 0.2 bar, vacuum impregnation was performed using a nano-epoxy resin solution for 60 minutes.
[0114] 1.5% nano titanium dioxide is added to the polymer solution to improve corrosion resistance.
[0115] 4. Curing and interface enhancement
[0116] Curing at 50℃ for 4 hours.
[0117] 5% silane coupling agent solution was sprayed on the aggregate surface with a spraying thickness of 40 μm and air-dried for 12 hours at 25°C.
[0118] Application: This reinforced aggregate is used in the production of precast components such as bridge structures, tunnel linings, etc. to enhance compressive strength and durability.
[0119] Example 5: Preparation of reinforced aggregate for antifreeze refractory materials
[0120] 1. Aggregate pretreatment
[0121] Select granite aggregate with a particle size of 5-20 mm and wash it with distilled water for 25 minutes.
[0122] Soak in 0.5M NaOH solution for 20 minutes, control the temperature at 30℃, rinse and dry at 80℃ for 8 hours.
[0123] 2. Chemical modification
[0124] Soak the aggregate in 8 mol / L NaOH solution for 60 minutes.
[0125] The particle size of nano silica fume is 50nm, which is added at 7% of the mass of the aggregate and dispersed by ultrasonic for 40 minutes.
[0126] After soaking for 60 min, the aggregate was heat treated at 80 °C for 5 h to generate CSH gel.
[0127] 3. Polymer impregnation
[0128] Under a vacuum environment of 0.3 bar, the nano-polyurethane solution was used for impregnation for 60 minutes.
[0129] 2.5% nano zinc oxide is added to the polymer solution to improve the frost resistance and fire resistance of the aggregate.
[0130] 4. Curing and interface enhancement
[0131] Curing at room temperature for 24 hours.
[0132] 3% silane coupling agent solution was sprayed on the aggregate surface with a spraying thickness of 30 μm and air-dried for 6 hours at 25°C.
[0133] Application: This reinforced aggregate is used in antifreeze and fire-resistant materials, suitable for concrete structures in cold areas or thermal insulation materials in high temperature environments.
[0134] Comparative Example 1: Preparation of Aggregate without Nano-Silica Fume Modification
[0135] Compared with Example 1, the only difference is that the nano-silica fume modification treatment is skipped, and the remaining steps are the same.
[0136] Comparative Example 2: Using traditional silica fume instead of nano silica fume
[0137] Compared with Example 1, the only difference is that conventional silica fume with a particle size of 1-5 μm is used instead of nano silica fume, 7% of the mass of the aggregate is added to the solution, stirred for 30 minutes, and no ultrasonic dispersion treatment is performed. The remaining steps are the same.
[0138] Comparative Example 3: No vacuum assisted polymer impregnation
[0139] Compared with Example 1, the only difference is that the aggregate is directly placed in a normal pressure environment and immersed in the polyurethane solution for 60 minutes without vacuum assistance, and the other steps are the same.
[0140] Comparative Example 4: No silane coupling agent interface enhancement treatment
[0141] Compared with Example 1, the only difference is that the silane coupling agent treatment is skipped and the aggregate is directly used for testing, and the other steps are the same.
[0142] Comparative experiment 1: compressive strength test
[0143] Experimental equipment:
[0144] Compression strength testing machine (pressing head speed: 1mm / min, maximum pressure: 50kN)
[0145] Sample preparation equipment (screening equipment, drying equipment, vacuum impregnation equipment, etc.)
[0146] Experimental steps:
[0147] 1. Prepare samples: Prepare aggregate samples according to the method of Example 1 and 4 comparative examples of the present invention (3 samples are prepared in each group).
[0148] 2. Test preparation: After 28 days of curing, each group of prepared aggregate samples is placed on a compressive strength testing machine.
[0149] 3. Compressive strength test: Use a compressive strength testing machine to gradually apply pressure at a speed of 1mm / min, record the maximum load when each sample is destroyed, and calculate the compressive strength.
[0150] 4. Result recording: Take 3 samples from each group, record the compressive strength of each sample, and calculate the average value.
[0151] The experimental data are shown in the following table:
[0152]
[0153] From the data in the above table, we can get:
[0154] The compressive strength of Example 1 (75.2 MPa) of the present invention is significantly improved compared with the four comparative examples. This shows that the present invention effectively improves the overall strength of the aggregate through the steps of nano-silica fume modification, vacuum-assisted polymer impregnation and silane coupling agent interface enhancement.
[0155] Comparative Example 1 (55.4 MPa): The strength of the aggregate without nano-silica fume modification is low, which proves that nano-silica fume modification plays an important role in filling the micropores of the aggregate and enhancing the compactness of the aggregate structure. The volcanic ash reaction of nano-silica fume generates CSH gel, which makes the pore structure of the aggregate more compact and significantly improves the strength of the aggregate.
[0156] Comparative Example 2 (62.3 MPa): Although traditional silica fume was used, its particle size was large and no ultrasonic dispersion treatment was performed, resulting in the inability of the silica fume to effectively penetrate into the micropores of the aggregate, and the filling effect was limited. Compared with the nano silica fume of the present invention, the modification effect of traditional silica fume was significantly poorer. Nano silica fume has a small particle size and can penetrate into the tiny pores of the aggregate, further enhancing the strength of the aggregate.
[0157] Comparative Example 3 (58.4 MPa): Vacuum-assisted impregnation was not used, resulting in unsatisfactory penetration of the polymer into the aggregate. Vacuum-assisted impregnation allowed the polymer to penetrate into the micropores and cracks inside the aggregate, forming a uniform cross-linked network structure, which greatly improved the compressive strength of the aggregate. Impregnation under normal pressure prevented the polymer from penetrating deeply, resulting in the failure to fully enhance the aggregate structure.
[0158] Comparative Example 4 (68.1 MPa): No silane coupling agent interface enhancement treatment was performed, resulting in weak interface bonding of the aggregate. The silane coupling agent can combine with the aggregate surface and the chemical groups in the polymer through its active groups, significantly improving the bonding between the aggregate and the matrix material, thereby improving the compressive strength. Although the strength is higher than that of other comparative examples, the interface bonding is poor and is still not as good as Example 1 of the present invention.
[0159] The nano silica fume used in the present invention has a small particle size (50-100nm), can effectively fill the micropores of the aggregate, and react with calcium ions in the aggregate to form CSH gel. This reaction makes the pore structure of the aggregate more compact and improves the compressive strength of the aggregate. However, due to the large particle size of traditional silica fume, it cannot deeply fill the micropores, resulting in its modification effect being inferior to that of nano silica fume.
[0160] Under vacuum conditions, polymers can more effectively penetrate into the pores inside the aggregate and form a uniform and dense cross-linked network structure after curing. Compared with normal pressure impregnation, vacuum impregnation can eliminate the air inside the aggregate, ensuring that the polymer can fully penetrate, thereby significantly enhancing the mechanical properties of the aggregate.
[0161] Silane coupling agent enhances the bonding force between aggregate and matrix material through its chemical structure. Its mechanism of action is that the functional groups of silane coupling agent combine with the chemical groups on the surface of aggregate to form strong chemical bonds, which significantly improves the interface strength between aggregate and matrix material, thereby improving the compressive performance of the overall material.
[0162] In summary, the present invention forms a multi-level and multi-step strengthening mechanism through nano-silica fume modification, vacuum-assisted polymer impregnation and silane coupling agent interface reinforcement. Each step works synergistically, so that the aggregate of the present invention has significantly better mechanical properties than the comparative example, especially in terms of compressive strength.
[0163] Comparative experiment 2: Durability test (freeze-thaw resistance)
[0164] Experimental equipment:
[0165] Freeze-thaw cycle test chamber (temperature range: -20℃ to 20℃, temperature rise and fall rate is controllable)
[0166] Precision electronic balance (accuracy 0.01g)
[0167] Compression strength testing machine
[0168] Maintenance equipment (temperature controlled at 20±2℃, humidity ≥95%)
[0169] Experimental steps:
[0170] 1. Prepare the sample:
[0171] Aggregate samples were prepared according to the methods of Example 1 of the present invention and four comparative examples, with 3 samples in each group.
[0172] 2. Initial weight measurement:
[0173] After 28 days of curing, the initial weight of each aggregate sample was measured using a precision electronic balance and the data were recorded.
[0174] 3. Freeze-thaw cycle experiment:
[0175] Each group of samples was placed in a freeze-thaw cycle test chamber and subjected to 50 freeze-thaw cycles. Each cycle included:
[0176] Freezing stage: the temperature was lowered to -20°C and maintained for 2 hours.
[0177] Melting stage: temperature rises to 20°C and maintains for 2 hours.
[0178] The heating and cooling rate of each freeze-thaw cycle was controlled at 3°C / min.
[0179] 4.Weight change measurement:
[0180] After 50 freeze-thaw cycles, the samples were taken out of the freeze-thaw chamber, and the weight of each sample was measured again using a precision electronic balance, and the weight change was recorded.
[0181] 5. Compressive strength test:
[0182] After freeze-thaw cycles, a compressive strength testing machine was used to gradually apply pressure at a rate of 1 mm / min to measure the compressive strength of each sample. The results were compared with the compressive strength before freeze-thaw to calculate the strength loss.
[0183] 6. Data recording and calculation:
[0184] Record the weight change (weight loss rate) and compressive strength change (strength loss rate) of each specimen, and calculate the average value for each group of samples.
[0185] The experimental results are shown in the following table:
[0186]
[0187] From the data in the above table, we can get:
[0188] The freeze-thaw resistance of Example 1 of the present invention is the best. After 50 freeze-thaw cycles, the weight loss rate is only 0.50%, and the strength loss rate is 3.19%. This shows that through nano-silica fume modification, vacuum-assisted polymer impregnation and silane coupling agent treatment, the structure of the aggregate is well maintained during the freeze-thaw cycle, and the durability is significantly enhanced.
[0189] Comparative Example 1 (no silica fume modification): The weight loss rate is 3.25%, and the strength loss rate reaches 14.06%, indicating that the aggregate without nano-silica fume modification shows greater degradation during freeze-thaw cycles. The modification of nano-silica fume fills the microporous structure of the aggregate, and forms a dense CSH gel layer through the volcanic ash reaction, which prevents the penetration and freezing expansion of water in the aggregate and significantly improves the freeze-thaw resistance. The aggregate without silica fume modification has more pores, and water can easily penetrate, resulting in severe freeze-thaw damage.
[0190] Comparative Example 2 (traditional silica fume): The weight loss rate is 2.08%, and the strength loss rate is 10.59%. Although traditional silica fume is used, due to the large particles and the lack of ultrasonic dispersion treatment, the silica fume cannot penetrate deeply into the micropores of the aggregate, and the filling effect is not ideal. During the freeze-thaw process, the aggregate modified by traditional silica fume still has large pores, and the intrusion of water leads to the degradation of the aggregate structure. Therefore, the use of nano silica fume and its full dispersion are important factors in improving the freeze-thaw resistance of aggregate.
[0191] Comparative Example 3 (without vacuum impregnation): weight loss rate is 2.89%, strength loss rate is 13.87%. Without vacuum-assisted polymer impregnation, the polymer cannot penetrate deeply into the micropores and cracks of the aggregate. During the freeze-thaw cycle, water can enter these unfilled pores, resulting in increased freeze-thaw damage. Vacuum-assisted impregnation can effectively remove the air inside the aggregate, allowing the polymer to penetrate deeply, forming a uniform and dense protective layer, and significantly improving the freeze-thaw resistance of the aggregate.
[0192] Comparative Example 4 (no silane coupling agent treatment): weight loss rate is 1.40%, strength loss rate is 8.96%. Although the lack of silane coupling agent treatment has little effect on weight loss, it has a greater impact on the loss of compressive strength. Silane coupling agent effectively avoids the generation of interface cracks during freeze-thaw cycles by enhancing the interfacial adhesion between aggregate and matrix material, thereby improving freeze-thaw resistance. After freeze-thaw cycles, the interfacial adhesion of aggregates that have not been treated with coupling agents is weakened, resulting in a decrease in compressive strength.
[0193] The nano silica fume used in the present invention generates CSH gel through volcanic ash reaction, which significantly enhances the compactness of aggregate, fills micropores, and prevents water penetration and freezing expansion. Compared with traditional silica fume, nano silica fume has a smaller particle size and can fill the micropores of aggregate more deeply to form a dense gel layer, which significantly improves the freeze-thaw resistance of aggregate.
[0194] Vacuum impregnation can effectively remove the air in the pores of aggregates, allowing the polymer to penetrate deeply into the micropores and cracks of aggregates. The dense cross-linked network structure formed after the polymer solidifies can prevent water from penetrating into the aggregate, reduce water intrusion and expansion pressure during freeze-thaw cycles, and thus significantly improve the freeze-thaw resistance of aggregates.
[0195] Silane coupling agent enhances the interfacial bonding between aggregate and matrix material through chemical bonding, effectively avoiding cracks and peeling of the interface during freeze-thaw cycles. During freeze-thaw cycles, the strong bonding of the interface prevents moisture from entering the interface area, reduces the relative displacement between aggregate and matrix material, and thus reduces freeze-thaw damage.
[0196] In summary, the present invention effectively improves the freeze-thaw resistance of aggregates through nano-silica fume modification, vacuum-assisted polymer impregnation and silane coupling agent interface enhancement treatment. The synergistic effect of each step significantly reduces the water intrusion and aggregate structure degradation during the freeze-thaw cycle, and significantly improves the durability of aggregates.
[0197] Comparative experiment 3: interface adhesion test
[0198] Experimental equipment:
[0199] Direct pull-out testing machine (maximum pull-out force: 50kN, accuracy: 0.1kN)
[0200] Cement mortar (ratio: water-cement ratio 0.4, sand-cement ratio 3:1)
[0201] Moulds and curing equipment
[0202] Experimental steps:
[0203] 1. Sample preparation:
[0204] Aggregate samples were prepared according to the methods of Example 1 of the present invention and four comparative examples, with 3 samples in each group.
[0205] 2. Preparation of cement mortar samples:
[0206] Cement mortar was prepared according to standard method using a mix ratio of water-cement ratio of 0.4 and sand-cement ratio of 3:1.
[0207] The prepared aggregates were embedded in cement mortar to ensure that the aggregates were in full contact with the surface of the mortar. Three samples were prepared for each group and placed in a standard curing room for 28 days (temperature 20±2°C, humidity ≥95%).
[0208] 3. Direct pull-out test:
[0209] After 28 days of curing, each group of samples was placed in a direct pull-out test machine, and a vertical pull-out force was applied. The pull-out rate was controlled at 0.5 mm / min, and the maximum pull-out force at failure was recorded.
[0210] The bond strength at the interface between aggregate and cement matrix was tested and the average bond strength of each group was calculated.
[0211] 4. Data recording and analysis:
[0212] The maximum pull-out force of each sample was recorded and the average bond strength was calculated in MPa.
[0213] The experimental results are shown in the following table:
[0214]
[0215]
[0216] From the data in the above table, we can get:
[0217] Example 1 of the present invention (4.79 MPa) exhibits the highest interfacial bonding strength. The present invention uses nano-silica fume modification, vacuum-assisted polymer impregnation, and silane coupling agent interfacial enhancement treatment to significantly improve the bonding between aggregate and matrix material (such as cement). This shows that these innovative steps play an important role in improving the bonding between aggregate and matrix material.
[0218] Comparative Example 1 (3.38 MPa): The bonding strength of the aggregate without nano-silica fume modification is significantly lower, indicating that the modification of nano-silica fume is crucial to enhancing the interfacial bonding strength. The volcanic ash reaction of nano-silica fume generates CSH gel on the surface of the aggregate, which effectively increases the chemical bonding strength between the aggregate and the cement matrix. The surface of the aggregate without silica fume modification is relatively smooth, and the bonding with the cement matrix mainly relies on physical adhesion, resulting in low interfacial strength.
[0219] Comparative Example 2 (3.70 MPa): Using traditional silica fume instead of nano silica fume, although the bonding strength is improved to a certain extent, the effect is not as good as the present invention. This is because the particle size of traditional silica fume is large and cannot effectively fill the micropores on the surface of the aggregate, and the bonding force between the silica fume and the matrix is weak. The particle size of nano silica fume is small and can penetrate into the micropores of the aggregate. The CSH gel layer generated by the reaction increases the active functional groups on the surface of the aggregate, significantly enhancing the bonding with the cement matrix.
[0220] Comparative Example 3 (3.60 MPa): Vacuum-assisted polymer impregnation was not used, resulting in a significant decrease in interfacial bonding strength. Vacuum-assisted impregnation can remove air from the aggregate surface, allowing the polymer to penetrate deeper into the micropores and cracks of the aggregate, forming a dense cross-linked network structure, which significantly enhances the strength and adhesion of the aggregate surface. Normal pressure impregnation cannot fully penetrate, resulting in uneven polymer coverage, which affects the bonding strength.
[0221] Comparative Example 4 (3.98 MPa): Although the bonding strength of the aggregate not treated with silane coupling agent is close to that of the present invention, there is still a significant gap. The silane coupling agent chemically combines with the chemical functional groups on the surface of the aggregate through its functional groups, and at the same time, its organic groups interact with the cement matrix, which significantly enhances the interfacial bonding strength. For aggregates without silane coupling agent, the interfacial bonding relies more on physical force and lacks chemical bonding, resulting in lower interfacial strength.
[0222] The nano silica fume used in the present invention generates a CSH gel layer through its volcanic ash reaction, which significantly enhances the surface activity of the aggregate. This layer of gel enhances the chemical bonding between the aggregate and the cement matrix, and further enhances the interfacial bonding. Compared with traditional silica fume, the nano silica fume has a smaller particle size and can fill the micropores on the surface of the aggregate, making the interface denser.
[0223] Vacuum impregnation removes the air on the surface of the aggregate, allowing the polymer to penetrate deeply into the micropores and cracks of the aggregate, forming a uniform and dense cross-linked network structure. This structure not only improves the strength of the aggregate itself, but also forms a layer of polymer film at the interface, effectively enhancing the adhesion between the aggregate and the cement matrix. Under normal pressure, the polymer does not penetrate sufficiently, resulting in weak interface bonding.
[0224] Silane coupling agent forms a chemical bond on the surface of aggregate, combines with the hydroxyl group on the surface of aggregate through its siloxy group, and interacts with the cement matrix through organic groups to form a strong chemical bond. Silane coupling agent not only enhances the bonding force on the surface of aggregate, but also avoids cracks and spalling at the interface by enhancing the chemical compatibility between aggregate and matrix material, thus significantly improving the bonding strength.
[0225] In summary, the present invention forms a multiple reinforcement mechanism through nano-silica fume modification, vacuum-assisted polymer impregnation and silane coupling agent interface reinforcement treatment, which significantly improves the interfacial adhesion between aggregate and cement matrix. The synergistic effect of each step makes the aggregate of the present invention superior to the comparative example in terms of interfacial bonding strength, especially showing excellent mechanical properties in cement-based materials.
[0226] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A preparation method for improving aggregate strength, characterized in that: The following steps are involved: 1) Select natural coarse aggregate with a particle size of 5-20 mm and perform pretreatment of cleaning, alkali solution soaking and drying; 2) Soak the pretreated aggregate in 8-12 mol / L NaOH solution for 60-120 minutes and modify it with nano-silica fume; 3) heat treating the aggregate at 70-100°C for 3-5 hours to generate CSH gel; 4) Place the dried aggregate in a vacuum environment of 0.1-0.3 bar, add nano polyurethane or epoxy resin polymer solution, and immerse for 60-90 minutes; 5) Curing the polymer-impregnated aggregate at 20-25°C for 12-24 hours; 6) Spraying the aggregate surface after polymer curing with 3-5% silane coupling agent solution and air drying for 6-12 hours.
2. A preparation method for improving aggregate strength according to claim 1, characterized in that: The pre-processing comprises: Use distilled water to wash for 20-30 minutes to remove impurities on the surface of the aggregate; Soak the cleaned aggregate in 0.5M NaOH solution at a temperature of 25-35°C for 10-20 minutes; After soaking in alkali solution, the aggregate is repeatedly washed with distilled water until the pH value of the filtrate is close to neutral, and then dried at 60-80℃.
3. A preparation method for improving aggregate strength according to claim 1, characterized in that: In the nano-silica fume modification step, the particle size of the nano-silica fume is 50-100 nm, and it is added at 3-7% of the mass of the aggregate, and is evenly dispersed in the solution through ultrasonic dispersion and stirring.
4. A preparation method for improving aggregate strength according to claim 3, characterized in that: In the modification of the nano-silica fume, the nano-silica fume solution also contains 1-2% sodium silicate.
5. A preparation method for improving aggregate strength according to claim 1, characterized in that: In the polymer impregnation step, the vacuum degree is set to 0.1-0.3 bar, the impregnation time is 60-90 minutes, and a low-frequency vibration device is used with a frequency of 5-10 Hz.
6. A preparation method for improving aggregate strength according to claim 1, characterized in that: A nano-enhancing material is also added to the polymer solution. The nano-enhancing material is nano-titanium dioxide or nano-zinc oxide, and the adding ratio is 1-3% of the mass of the polymer solution.
7. A preparation method for improving aggregate strength according to claim 1, characterized in that: The polymer curing step includes curing at room temperature of 20-25° C. for 12-24 hours, or thermal curing at 50-80° C. for 4-8 hours.
8. A preparation method for improving aggregate strength according to claim 1, characterized in that: The step 6) comprises spraying a 3-5% concentration silane coupling agent solution on the aggregate surface with a spraying thickness of 20-40 μm, and air-drying at 20-25° C. for 6-12 hours.
9. A reinforced aggregate prepared by the method according to any one of claims 1 to 8.
10. A method for preparing reinforced concrete, characterized in that: The method comprises applying the reinforced aggregate according to claim 9 to a cement-based composite material.
Citation Information
Cited By
Freeze-thaw-resistant repair material for hydraulic engineering tunnel structure and preparation method thereof
CN121850584A
A freezing-thawing resistant type repair material for hydraulic engineering tunnel structures and a preparation method thereof
CN121850584B